The role and significance of career development fund in strengthening library talent - Hassan Basri, Jamilah; Ghadzali, Mohd Pisol; Ibrahim, Nor Azan (Universiti Malaya, 2012)
Career Development Fund (TKKSP) was established in 1984 in Universiti Sains Malaysia Library. The initiatives of the fund began from the idea of Chief Librarian Lim Huck Tee to serve and assist library staff in the development of their career and vocational skills. From the beginning, the funds are made possible through the generosity of the professional staff and librarians in USM libraries. The purpose of these funds is to support career enhancing acavities and monies from the fund are expanded to provide total support for library staff to participate in job and career related development acavities. Library staff is encouraged to utilize the fund wherever they believe the participation will contribute to their personal and professional career growth in the field of librarianship and other discipline as well as strengthening their vocational preparation.